Black Freethinkers : A History of African American Secularism - Cameron, Christopher, 1983- (Book collections on Project MUSE., 2019)
"This book is a political and intellectual history of black freethought during the nineteenth and twentieth centuries. Beginning its analysis in the era of slavery, "Black Freethinkers" demonstrates an alternative origin to nonbelief and religious skepticism in America, namely the brutality of the institution of slavery. The book then turns to the growth of atheism and agnosticism among African Americans in two major political and intellectual movements of the 1920s: the New Negro Renaissance and the growth of black socialism and communism. A final chapter explores the critical importance of freethought among participants in the Civil Rights and Black Power movements of the 1960s and 1970s. Key figures in this narrative include well-known people such as Frederick Douglass, Zora Neale Hurston, James Baldwin, and Alice Walker, as well as lesser known thinkers such as Louise Thompson Patterson, Sarah Webster Fabio, and David Cincore. The study employs a diverse array of sources, including slave narratives, travel accounts, novels, poetry, memoirs, newspapers, and archival sources such as church records, sermons, and letters. The central argument of the book is that freethought, which includes atheism, agnosticism, and non-traditional religious orientations such as deism and paganism, has been a central component of black political and intellectual life from the 19th century to the present. Contrary to historical and popular depictions of African Americans as naturally religious, this study demonstrates the great diversity in black religious thought and makes an important contribution to our understanding of black intellectual history"--